Analisis Kinerja Keuangan Pada Perusahaan Fintech Lending Berizin Otoritas Jasa Keuangan - Mariani Br Berutu; Abrar Amri; Rimal Mahdani (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return on Assets (ROA) as a measure of financial performance in licensed Fintech Lending companies registered with the Financial Services Authority (OJK) for the period 2021–2023. The rapid growth of the fintech industry, particularly peer-to-peer (P2P) lending services, highlights the need for evaluating financial performance through financial statement analysis. This research adopts a quantitative approach using multiple linear regression on 38 financial reports published by OJK. The results indicate that, partially, CAR and NIM have a significant influence on ROA, while LDR does not. Simultaneously, the three independent variables CAR, LDR, and NIM have a significant effect on the financial performance of Fintech Lending Financial Services Authority (OJK) for the period 2021–2023.